Secondary Post Partum Hemorrhage Associated with Cervical Cancer: A Case Report - Hubert Halim; Gede Alit Wardana (International Journal Labs, 2025)
Cervical cancer is one of the major causes of cancer-related death in women worldwide. It is the fourth most diagnosed malignancy, responsible for approximately 604,000 new cases and 342,000 deaths annually worldwide. Rarely does occur in post partum period. We presented a case of a 26 years old woman, Para 1 came with complaints of frequent vaginal bleeding. Her history included one previous caesarean sections without any serious complication. The caesarean section was performed on the patient 23 days before admission. Two weeks following the procedure, she began to experience vaginal bleeding. History of pap smear examinations was absent. There was no prior history of placenta abnormalities or vaginal bleeding during pregnancy. Along with the unrelenting vaginal bleeding, curettage and biopsy was perfomed 30 days after the c-section surgery. Cervical tissue were sent to Anatomical Pathology (PA) laboratory for examination after the surgery. The patient was discharge with a stable condition one day after surgery. One week later, the definitive diagnosis based on conclusion of histopathological findings was a cervical adenosquamous carcinoma. Several risk factors are linked to the increase in the prevalence of cervical cancer. These include initiating sexual activity under the age of 16 years, having multiple sexual partners and infrequent condom use, prolonged use (more than 5 years) of oral contraceptive pills, having a weakened immune system (including being HIV positive), low socioeconomic status, and smoking. In this case, the patient was 28 years old, which unusual for the cervical cancer develop in this age.